2018
DOI: 10.1007/s11419-018-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Forensic analysis using ultra-high-performance liquid chromatography–tandem mass spectrometry with solid-phase extraction of α-solanine and α-chaconine in whole blood

Abstract: PurposeThe potato glycoalkaloids (PGAs), α-solanine and α-chaconine can exert adverse effects on human health when consumed in excess. This study aimed to investigate the optimal extraction method for the quantitative analysis of PGAs in whole blood by using ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) and to apply this validated method to postmortem blood.MethodsA total of 200 µL of human whole blood was prepared for PGA extraction. For validation, a solid-phase extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Hossain et al (2015) reported LOQs for a-solanine and a-chaconine of 2 lg/L in potato extract, corresponding to 40 lg/kg in dehydrated potato powder. Nara et al (2019) reported an LOQ of 1 and 2 lg/L in whole blood for a-solanine and a-chaconine, respectively.…”
Section: Lc-ms Methods (Lc-ms/ms Lc-hrms)mentioning
confidence: 99%
See 2 more Smart Citations
“…Hossain et al (2015) reported LOQs for a-solanine and a-chaconine of 2 lg/L in potato extract, corresponding to 40 lg/kg in dehydrated potato powder. Nara et al (2019) reported an LOQ of 1 and 2 lg/L in whole blood for a-solanine and a-chaconine, respectively.…”
Section: Lc-ms Methods (Lc-ms/ms Lc-hrms)mentioning
confidence: 99%
“…Combined with the high sensitivity of modern mass spectrometers, sample preparation and clean-up can often be minimised and simple dilution of extracts may be sufficient. Methods based on LC coupled to tandem mass spectrometry (LC-MS/MS) are often used for targeted analysis of GAs (Jandri c et al, 2011;Hossain et al, 2015;Nara et al, 2019), while methods using LC coupled to high resolution MS (LC-HRMS) or to Orbitrap MS (LC-Orbitrap-MS) are more commonly used for metabolomic studies and exploratory research (Moco et al, 2007;Caprioli et al, 2014). Hossain et al (2015) reported LOQs for a-solanine and a-chaconine of 2 lg/L in potato extract, corresponding to 40 lg/kg in dehydrated potato powder.…”
Section: Lc-ms Methods (Lc-ms/ms Lc-hrms)mentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of each glycoalkaloid in pooled human serum were 0.067 ± 0.013 ng/mL for α-solanine, 0.33 ± 0.11 ng/mL for α-chaconine, and 0.60 ± 0.17 ng/mL for solanidine (Table S5). The concentrations of these glycoalkaloids were significantly lower than those in the blood of glycoalkaloid poisoning cases in previous studies [ 29 , 32 ], suggesting that the glycoalkaloids detected in the pooled human serum used in this study would be derived from a daily diet. These results confirmed that our method could detect glycoalkaloids even at sub-ppb concentration levels.…”
Section: Resultsmentioning
confidence: 51%
“…All the solutions were stored at À20 C in darkness when not in use. 27 Working standard solutions were prepared by serial diluting the mixed stock solutions with methanol and were stored at 4 C. A blank matrix of fingerprints was collected from healthy volunteers after they had provided informed consent, and the samples were screened for the 17 hypoglycemic drugs all of which were confirmed to be negative. Matrix-matched solutions were prepared by diluting the mixed stock solutions with the blank matrix and were stored at 4 C in the same way.…”
Section: Preparation Of Standardsmentioning
confidence: 99%